SUPERIOR PERMISSION IN DIVORCE FOR CIVIL SERVANTS FROM THE VIEW OF RELIGIOUS LAW - Dumaria Evi Mawartiku Palamarta Br. Gultom; Rosnidar Sembiring; Yefrizawati; Afnila (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Divorce is a complex problem in married life. Whatever problems occur in the household, whether in state law or religious law in force in Indonesia, divorce is the last way to solve them. Divorce can only be carried out before the court if the court fails to reconcile the two parties through mediation. Basically, civil servant divorce is the same as other communities, but the difference is that civil servants must first obtain permission from their superiors before carrying out the divorce. Civil servants must ask their superiors for permission through a hierarchical system, which takes a long time to get permission to divorce. If you look at these requirements for civil servants who are going to divorce, it is very difficult, but if divorce is the only way, then it is certain that the civil servant will receive sanctions. And in practice, permission from superiors as a requirement for civil servant divorce is difficult to issue from superiors who wish to divorce. So that in some cases the court gave divorce decisions to Civil Servants without a letter of permission from their superiors. Whereas in legal religious law in Indonesia, divorce can occur if the terms and conditions are met. This is the topic of the problem that the author wants to examine in this paper. What becomes the formulation of the problem is how is the superior's permission in civil servant divorce from the point of view of religious law? The legal research method used is normative juridical, namely a scientific research procedure to find the truth based on the scientific logic of law from a normative perspective. The approach used is a statutory approach related to the subject matter involved. If viewed from the point of view of religious law that is recognized in Indonesia (Islam and Non-Islam), divorce is indeed not recommended in the rules of religious law, but if circumstances demand this to happen then one must follow the rules and reasons determined by every legal religion in Indonesia. Because this concerns a person's right to determine a peaceful, secure and prosperous life. Through the research process above, it can be concluded that the decision in determining divorce is always given to the decision of each individual. Because freedom in determining life choices and being able to take responsibility for every risk of that choice. Every rule in the official religion in Indonesia considers divorce not a recommended action but if in reality divorce is the final solution, the rules in religion will not prevent it. This is the real basis for each individual, including State Civil Apparatus, in choosing a decision in their marriage, namely ending it in divorce. Permission from superiors is only an obstacle to solving problems in the household of an State Civil Apparatus. From this article, it is hoped that in the future, permission from superiors in the event of an State Civil Apparatusdivorce does not interfere in principled matters in the marital life of its employees, but is only administrative in nature. So that the goal of a peaceful and prosperous State Civil Apparatuslife can be carried out properly.